Review of Enfermería Mandálica, un modelo cultural de intervención en Atención Primaria, by Pedro M. Salas Iglesias - Luis Cibanal Juan (Universidad de Alicante, 2019)
This review describes the characteristics of mandálica nursing in the context of primary care nursing.